Fluid friction/heat transfer irreversibility and heat function study on MHD free convection within the MWCNT–water nanofluid‐filled porous cavity. Issue 5 (2nd March 2022) - Kumar, Alagarsamy Vanav; Lawrence, Jino; Saravanakumar, G.
Abstract: The study comprises the effect of natural/free convection on an MWCNT–water nanofluid‐filled cavity. The porous cavity is heated/cooled to the left/right walls and the horizontal wall is maintained adiabatically. The flow behavior and entropy analysis are evaluated numerically using the finite difference approximation techniques. This study is bounded with various dimensional parameters such as ϕ φ —nanoparticle concentration, Ha —Hartmann number, Ra —Rayleigh number, and Da —Darcy number. The results of the study are illustrated using ψ ψ —streamlines or stream function, θ θ —isotherms, Π Π —heatlines or heat function, S ψ S_ψ —fluid friction irreversibility, S θ S_θ —heat transfer irreversibility, Θ cup Θ _cup —cup‐mixing temperature, and Θ RMSD Θ _RMSD —root‐mean‐square deviation. Also, Nu Nu —average Nusselt number and Be Be —average Bejan number are used to represent the transfer rate of heat and irreversibility of fluid friction/heat transfer, respectively. The domination of conduction on lower Ra and Da are noticed and, domination of convection on higher Ra and Da are observed using a heatline map. The fluid friction and heat transfer irreversibilities are highly noted near the vertical boundaries for increasing Rayleigh number and Darcy number.